PEMBERIAN AIR SUSU IBU (ASI) DAN DEXTROSE 5 % UNTUK MENGURANGI NYERI PEMASANGAN INFUS PADA NEONATUS (BREAST MILK AND DEXTROSE 5% TO REDUCE THE PAIN OF INFUSION IN NEONATES) - Witri Hastuti; Sri Pujiwati; Retno Apriliyanti (Indonesian National Nurses Association (INNA) of Central Java, 2021)
Neonates in perinatology room of Wongsonegoro Hospital were 879 babies from August 2019 to July 2020 and 459 (52%) had infusions attached. Total of 459 infants were given intravenous lines, found 11 (2,3%) cases of failure in infusion. Failure causes the neonates cry because of pain. Based on this, the purpose of this study was to determine the effect of giving breastmilk and dextrose 55 %% on the pain response during infusion in neonates. This type of research is quasi experiment. The design of this study used a posttest with control group design. Population was neonates who received infusion therapy. Sampel of 32 neonates. The treatment group was given breast milk for 16 neonates and the control group was given Dextrose 5% for 16 neonates. This study used purposive sampling. The statistical test used the Mann Whitnesy test. The pain response of the breast milk treatment group in neonates was the mean value of 3.19. Pain response in the control group was the mean value of 4.31. There is an effect of giving breast milk the pain response during infusion in nenates p value=0.002. So it can be concluded that giving breast milk is more effective in reducing pain during infusion in neonates when compared to dextrose 5%.